In vitro and in silico analysis of new n-butyl and isobutyl quinoxaline-7-carboxylate 1,4-di-N-oxide derivatives against trypanosoma cruzi as Trypanothione reductase inhibitors - González-González, Alonzo; Sánchez-Sánchez, Oscar; Krauth-Siegel, Renate; Bolognesi, Maria Laura; Gớmez-Escobedo, Rogelio; Nogueda-Torres, Benjamín; Vázquez-Jiménez, Lenci K.; Saavedra, Emma; Encalada, Rusely; Espinoza-Hicks, José Carlos; Paz-González, Alma D.; Rivera, Gildardo (International journal of molecular sciences, 2022)
American trypanosomiasis is a worldwide health problem that requires attention due to ineffective treatment options. We evaluated n-butyl and isobutyl quinoxaline-7-carboxylate 1,4-di-N-oxide derivatives against trypomastigotes of the Trypanosoma cruzi strains NINOA and INC-5. An in silico analysis of the interactions of 1,4-di-N-oxide on the active site of trypanothione reductase (TR) and an enzyme inhibition study was carried out. The n-butyl series compound identified as T-150 had the best trypanocidal activity against T. cruzi trypomastigotes, with a 13% TR inhibition at 44 μM. The derivative T-147 behaved as a mixed inhibitor with Ki and Ki’ inhibition constants of 11.4 and 60.8 µM, respectively. This finding is comparable to the TR inhibitor mepacrine (Ki = 19 µM).
Gesehen am 20.01.2023